Association between normal weight obesity and comorbidities and events of cardiovascular diseases among adults in South China. - Miaomiao Ma; Deliang Lv; Xiaobing Wu; Yuqing Chen; Shimiao Dai; Yutian Luo; Hui Yang; Wei Xie; Fengzhu Xie; Qinggang Shang; Ziyang Zhang; Zhiguang Zhao; et al. (PLoS ONE)
Background The increased risks for cardiovascular comorbidities and cardiovascular diseases (CVD) in populations with normal weight obesity (NWO) have not been well-identified. We aimed to study their associations in an adult population in South China. Methods Based on the CVD prevalence of 4% in Shenzhen and a calculated sample size of 6,000, a cross-sectional study with a multi-stage stratified cluster sampling method was conducted in Shenzhen City. The cardiovascular comorbidities being studied were abdominal obesity (AO), diabetes, hypertension, dyslipidemia, metabolic syndrome, and chronic kidney disease, while the CVD events were occurrences of myocardial infarction and strokes. Questionnaire surveys, physical examinations, and laboratory tests were performed. NWO was defined as a condition with the highest tertile of body fat percentage (BF%) among the normal body mass index (BMI) range (18.5-23.9 kg/m2). Continuous data were reported as mean [standard deviation (SD)] and categorical data as percentages (%). CVD comorbidities and CVD events and their detection rates in different groups were compared using ANONA analysis and Chi-squared test. Spearman's correlation coefficients between BF% and cardiometabolic abnormalities were calculated by partial correlation analysis. Multivariate logistic regression models were used to estimate the odds ratios (ORs) and 95% confidence intervals (CIs) for BF%, CVD comorbidities, and CVD events, adjusted for multiple confounders. Results Among the total 6,240 subjects who completed the study and had BMI and BF% data available, 3,086 had normal BMI. The prevalence of NWO was 16.36%, with 13.15% for men and 19.54% for women. With confounders adjusted, the risks of AO (OR = 6.05, 95%CI = 3.40-10.75), essential hypertension (OR = 1.56, 95%CI = 1.09-2.22), dyslipidemia (OR = 1.85, 95%CI = 1.49-2.29), and metabolic syndrome (OR = 4.61, 95%CI = 2.32-9.18) were significantly increased in the populations with NWO compared with the population without NWO (P < 0.05). BF% was not significantly associated with the risk of CVD events in the total (OR = 1.56, 95%CI = 0.83-2.93), male (OR = 1.00, 95%CI = 0.44-2.30), and female populations (OR = 2.53, 95%CI = 0.91-7.06). Conclusion NWO was found to be positively associated with CVD comorbidities but not with CVD events. The current study provides a ground to conduct further studies on whether body fat affects the risk of occurrence of CVD events and the underlying mechanisms in the future.